Customer Loyalty and its Antecedents in Banking Service Rendering Context - Milan, Gabriel Sperandio; Eberle, Luciene; De Toni, Deonir; Olea, Pelayo Munhoz; Bebber, Suélen (Revista de Negócios, 2019)
In this research, customer loyalty was analyzed in the context of existing relationships between banking service providers and its customers. Therefore, a theoretical model was proposed and tested with banking service natural person customers taking into account perceived value, service provider reputation, trust, bonding tactics (financial, social and structural), and switching costs as customer loyalty antecedents. A multivariate statistical approach with structural equations modeling was used in a 1.026 customer sample of three major banks in Brazil. The results evidenced in the present research could serve as benchmarking for other researchers or managers connected to the financial service sector (or bank service) when looking for a better understanding of the antecedents of customer loyalty, adapting strategies and actions to stimulate and generate better market and economic-financial results for the institutions of this sector.